Hukum Bisnis Syariah dalam Perspektif Islam: Konsep, Prinsip, dan Implementasinya - Ahmad Syairi; Nor Aisah; Nadia Rahmah; Lahmudinur (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The study of fiqh muamalah covers regulations related to economic activities based on Islamic guidance, commonly known as Sharia business law. Although business objectives are often oriented toward profit, from a religious perspective such activities are also considered acts of worship when carried out with justice and honesty. The main focus of this discussion is the foundations of the Sharia-based commercial system, the core norms that underlie Islamic economic operations, and their application in the modern era. The review begins with a broad overview of business regulations rooted in the teachings of the Prophet, followed by an explanation of business as a moral action within the framework of tawhid. In the context of wealth, ownership is limited by ethical boundaries and collective responsibility. Also addressed are patterns of economic collaboration such as syirkah as well as other transactional agreements that uphold fair and professional relationships. The study concludes that the principles of Islamic business law integrate personal responsibility with collective objectives, while avoiding transactions involving interest, excessive speculation, or gambling. In today’s economic context, the implementation of these principles offers a path toward a business model that is not only aligned with religious values but also promotes equitable prosperity without relying on harmful schemes. Not all conventional approaches are able to achieve such a balance. Keywords: Sharia Business Law, Fiqh Muamalah, Islamic Business, Wealth Ownership, Business Cooperation, Sharia Contracts Abstrak Pengkajian fiqih muamalah mencakup aturan berkaitan dengan ekonomi menurut pedoman Islam, dikenal sebagai hukum bisnis syariah. Meskipun tujuan usaha sering kali adalah laba, dalam perspektif agama hal tersebut sekaligus tergolong ibadah bila dilakukan secara adil dan jujur. Pokok bahasan di sini ialah dasar-dasar sistem perniagaan syariah, norma inti yang mendasari operasi ekonomi Islami, beserta penerapannya di zaman kini. Tinjauan dimulai dari gambaran luas tentang ketentuan usaha berbasis ajaran Nabi, lalu ditambah posisi bisnis sebagai tindakan bermoral dalam ajaran tauhid. Dalam konteks harta, pemilikan dibatasi oleh batasan etika dan tanggung jawab kolektif. Tak luput dari pembicaraan: pola kolaborasi ekonomi semacam syirkah serta kesepakatan transaksi lainnya yang menjunjung relasi profesional berkeadilan. Pengkajian menyimpulkan: prinsip hukum bisnis Islam memadukan tanggung jawab pribadi dengan tujuan kolektif, sambil menjauhi transaksi mengandung bunga, spekulasi tinggi, atau perjudian. Dalam konteks ekonomi saat ini, terapan aturan tersebut membuka jalan bagi model usaha yang tidak hanya sesuai nilai agama tetapi juga mendukung kemakmuran secara adil tanpa bergantung pada skema merugikan. Tidak semua pendekatan konvensional mampu mencapai titik temu seperti ini. Kata Kunci : Hukum Bisnis Syariah, Fiqih Muamalah, Bisnis Islam, Kepemilikan Harta, Kerjasama Bisnis, Akad Syariah